2017
DOI: 10.1016/j.ultrasmedbio.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Using Speed of Sound Imaging to Characterize Breast Density

Abstract: A population of 165 women with negative mammographic screens also received an ultrasound tomography (UST) exam at the Karmanos Cancer Institute (KCI) in Detroit, MI. Standard statistical techniques were employed to measure the associations between the various mammographic and UST related density measures and various participant characteristics such as age, weight and height. The Mammographic percent density (MPD) was found to have similar strength associations with UST mean sound speed (Spearman coefficient, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 39 publications
1
51
0
Order By: Relevance
“…Prior to the work in this paper, ultrasound tomography had been explored as well for assessment of breast density although some of these methods provide a surrogate for QBD and not a direct percentage measure. Initial work using ultrasound tomography utilized images made from 2D‐based algorithms, wherein 2D images are concatenated together to yield 3D images . O'Flynn et al., Glide, and Duric et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the work in this paper, ultrasound tomography had been explored as well for assessment of breast density although some of these methods provide a surrogate for QBD and not a direct percentage measure. Initial work using ultrasound tomography utilized images made from 2D‐based algorithms, wherein 2D images are concatenated together to yield 3D images . O'Flynn et al., Glide, and Duric et al .…”
Section: Discussionmentioning
confidence: 99%
“…calculated volume‐averaged SOS (VASS) derived from ray‐based ultrasound tomography as a means to ascertain breast density. Similarly, Sak et al . used median and mean values of the SOS image and correlated with mammographic breast density as determined by Cumulus software.…”
Section: Discussionmentioning
confidence: 99%
“…Breast density has traditionally been measured using mammography, but more recently, ultrasound tomography (UST) sound speed images have also been shown to be an effective measure of breast density 4, 5 . UST has previously used a ray-based reconstruction method to produce sound speed images from which to make breast density measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Since HHUS can be time-consuming and suffers from repeatability problems [14], automated breast ultrasound (ABUS) devices, where the patient lies on a bed—either in a supine position and her breasts are compressed under gravity [15] or in a prone position [16]—have been developed [17] and tested [18]. With these two types of ABUS design, three-dimensional (3D) volumetric information is acquired, either by a linear B-mode ultrasound probe that scans across the breast in the frontal plane [15] or by a ring transducer immersed in water that moves upwards from the nipple to the chest wall [16].…”
Section: Introductionmentioning
confidence: 99%
“…With these two types of ABUS design, three-dimensional (3D) volumetric information is acquired, either by a linear B-mode ultrasound probe that scans across the breast in the frontal plane [15] or by a ring transducer immersed in water that moves upwards from the nipple to the chest wall [16]. Strong evidence to support the use of FFDM followed by ABUS, particularly in women with mammographically dense breasts, was recently published by Giuliano and Giuliano [19], who showed that the addition of ABUS resulted in the detection of 12.3 breast cancers per 1000 women screened compared to 4.6 per 1000 by FFDM alone.…”
Section: Introductionmentioning
confidence: 99%